Internalizing Pesantren Values to Prevent Violence Among Santri - Fathor Rozi; Muhammad Munif; Khodijatul Qodriyah; Alif Lailatul Mufidah (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
Bullying in Islamic boarding schools is a worrying phenomenon because it contradicts the main mission of Islamic boarding schools in shaping the character of students with noble morals. Although Islamic boarding schools are known as educational institutions based on religious values, bullying practices are still found in verbal, physical, and psychological forms. This study aims to examine how the internalization of Islamic boarding school values, particularly the trilogy and five awarenesses, plays a role in shaping an Islamic boarding school environment free from bullying practices. This study employs a qualitative approach, specifically a case study design, at the Nurul Jadid Islamic Boarding School. Data were collected through in-depth interviews, participatory observation, and documentation, involving Islamic boarding school administrators, foster parents, students, and regional heads as key informants. The findings show that open communication, sharing activities, daily sermons, and a spiritual-based reward and punishment system effectively shape the character of students who are empathetic and anti-violent. The contribution of this study lies in the development of a new perspective on preventing bullying based on religious values ​​that is contextual and applicable in Islamic education. These results are important because they show that cultural and spiritual approaches can be an effective and sustainable alternative in creating a safe and character-based educational environment.